Test and Analysis of Eccentric Shaft based on Secondary Projection Method - Wang Yin; Luo Shanming; Wen Quan; Gao Yongxiang; Liu Min (Jixie chuandong)
In order to improve the measurement accuracy of eccentric shaft,the eccentric shaft is tested and analyzed by secondary projection method. The measurement principle of the secondary projection method is analyzed. The projection data of the eccentric axes on the two planes perpendicular to each other are obtained by using the optical image measuring machine to perform the secondary projection measurement on the eccentric shaft. The projection data is processed to obtain the coordinate values of the center line end points of the eccentric axis in the spatial coordinate system,so as to further establish the true vector of the center line of each axis segment in space. According to the obtained vector data,the various parameters needed for the analysis of the eccentric shaft structure can be extracted,so that the eccentricity and concentricity of the eccentric shaft can be analyzed reasonably. The results show that the secondary projection method can greatly improve the measurement accuracy of the eccentric shaft.